HERBAL DRUGS AND THEIR EFFECT ON BIOCHEMICAL ATTRIBUTES OF CROSSBRED CALVES - RAM NIWAS,; D. P. SINGH,; V. K. PASWAN,; RIJPAL BISEN,; M. ABED ALBIAL, (The Bioscan, 2012)
The present investigation was planned to see the efficacy of self compounded and marketed herbal drugs on some of the biochemical attributes of crossbred calves. Those crossbred calves of 4 to 6 months of age having similar body weights were divided in to three groups comprising three calves in each. Three different trials were conducted in Rainy, winter and summer seasons and each trial was continued for 2 months excluding pre- experimental period. During each trial blood sample were collected directly from the jugular vein in the morning hr at the interval of 0, 30 and 60 days. It was observed that blood glucose level was significantly (p<0.05) higher in self compounded herbal drug (T2) group than marketed herbal drug (T3) and control groups (T1). A higher (p<0.05) level of cholesterol was observed in group fed with self formulated herbal drug as compared to marketed herbal drug and control groups. No significant (p<0.05) change was observed in total urea at day 0 and 30 but significant between 60 and 30 and 60 and 0 days of experiment. The SGOT was found significantly (p<0.05) higher in self compounded herbal drug treated calves than marketed herbal drug treated and control groups at 0, 30 and 60 days of trials. A significant (p<0.05) higher level of SGPT was observed due to adminis- tration of self formulated herbal drug as compared to marketed herbal drug and control groups. There was no significant (p<0.01) changes in SGOT and SGPT level at 0, 30 and 60 days of experiment.